Patterns of MUC1 tissue expression defined by an Anti-MUC1 cytoplasmic tail monoclonal antibody in breast cancer - Croce, María Virginia (2003)
Our aim was to determine the pattern of expression of MUC1 mucin cytoplasmic tail (MUC1 CT) in breast carcinoma. A total of 98 invasive breast adenocarcinoma tumor samples were assayed by immunohistochemical (IHC) analysis. The pattern of reaction was classified as membrane, cytoplasmic, or mixed. Subcellular fractions were prepared after SDS-PAGE and Western blotting. The antibodies employed were anti-MUC1 CT (CT2 monoclonal antibody, MAb) and C595 MAb against the extracellular MUC1 core protein. With the CT2 MAb, IHC showed a high percentage of positive staining in 93% of specimens, with membrane staining the most common pattern observed. C595 MAb was reactive in 73% of specimens. Similar percentages of membrane and cytoplasmic staining were found, mainly in a mixed pattern. Western blotting showed different bands. With the CT2 MAb, the membrane fraction showed the most intense reaction; a strong band of reaction was detected at approximately <30 kD. With the C595 MAb, in most cases a double band at 200 kD was found. In breast epithelium, the pattern of MUC1 CT expression may constitute an indicator of MUC1 production because it does not depend on glycosylation. The pattern and extension of MUC1 CT positivity do not vary according to the histopathological subtype of the tumor.